2021
DOI: 10.1001/jama.2020.26148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostic Yield of Exome Sequencing in Patients With Cerebral Palsy

Abstract: IMPORTANCE Cerebral palsy is a common neurodevelopmental disorder affecting movement and posture that often co-occurs with other neurodevelopmental disorders. Individual cases of cerebral palsy are often attributed to birth asphyxia; however, recent studies indicate that asphyxia accounts for less than 10% of cerebral palsy cases.OBJECTIVE To determine the molecular diagnostic yield of exome sequencing (prevalence of pathogenic and likely pathogenic variants) in individuals with cerebral palsy. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 45 publications
1
89
0
Order By: Relevance
“…In an article published recently in JAMA, Moreno-De-Luca and colleagues sought to determine the diagnostic yield of exome sequencing for CP. 3 This large cross-sectional study included results of exome sequencing performed in 2 settings. The first setting was a commercial laboratory in which samples were sent for analysis due to a diagnosis of CP, primarily in children (n = 1,345) with a median age of 8.8 years.…”
Section: Emerging Evidence Of a Genetic-cp Associationmentioning
confidence: 99%
See 3 more Smart Citations
“…In an article published recently in JAMA, Moreno-De-Luca and colleagues sought to determine the diagnostic yield of exome sequencing for CP. 3 This large cross-sectional study included results of exome sequencing performed in 2 settings. The first setting was a commercial laboratory in which samples were sent for analysis due to a diagnosis of CP, primarily in children (n = 1,345) with a median age of 8.8 years.…”
Section: Emerging Evidence Of a Genetic-cp Associationmentioning
confidence: 99%
“…Although most of the identified genetic variants were de novo (that is, they arose in the affected individual and were not clearly inherited), some were inherited from carrier parents. 3 A number of other recent studies also have investigated genetic causes of CP and similarly have reported that a substantial number of cases are genetic. Several studies that performed chromosomal microarray analysis in individuals with CP found deleterious copy number variants in 10% to 31% of cases.…”
Section: Emerging Evidence Of a Genetic-cp Associationmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of risk factors for CP have been identified, including prematurity, hypoxia-ischemia, placental insufficiency, chorio-amnionitis or other prenatal infection, perinatal inflammation, genetic causes, and combinations of these factors [ 6 , 7 , 8 , 9 ]. In particular, the presence of genetic variants have been investigated in some types of CP [ 10 , 11 ] with de novo copy number variants [ 12 , 13 , 14 , 15 , 16 , 17 ], single nucleotide variants [ 18 ], and de novo mutations [ 19 ] implicated in as many as 33% of the CP cases evaluated in those studies. Additional studies suggest that epigenetic alterations are associated with CP [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%